ANALISIS STABILITAS FREKUENSI GENSET GEDUNG AKIBAT FLUKTUASI BEBAN - Jendri Herman Sariadi Sigalingging; Muhammad Erpandi Dalimunthe; Adi Sastra Tarigan (CV. Hawari, 2026)
Generators are backup power sources that play a crucial role in maintaining a building's continuous electricity supply during disruptions to the main grid. Frequency stability is one of the parameters determining the quality of generator operation. This study aims to analyze the effect of load fluctuations on the frequency stability of building generators using a power system simulation method. Load variations were conducted at 25%, 50%, 75%, and 100% of the generator's capacity. Observed parameters included system frequency, frequency deviation, and governor response to load changes. The results showed that increasing the load caused the generator frequency to decrease from 49.95 Hz to 49.50 Hz, while the frequency deviation increased from 0.05 Hz to 0.50 Hz. However, all frequency values remained within the permissible operating tolerance limits of 49.5–50.5 Hz. The results indicate that the governor is capable of maintaining frequency stability, allowing the generator to operate reliably under various load conditions.